2020
DOI: 10.3390/molecules25102376
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Expression by Human Macrophage-Like Cells Derived from the Monocytic Cell Line THP-1 Differs between Treatment with Milk from Preterm- and Term-Delivering Mothers and Pasteurized Donor Milk

Abstract: Immunomodulatory proteins from human milk may enhance the protection and development of the infant’s gut. This study compared the immunomodulatory effects of treatment with milk from preterm-(PM) and term-delivering (TM) mothers and pasteurized donor milk (DM) on cytokine gene expression in human macrophage-like cells derived from the monocytic cell line THP-1. The gene expression of tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL-12 (p40), IL-10 and GAPDH in macrophages treated with PM, TM and DM at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A previous study used human milk at a 50 μg/mL concentration to study cytokine expression in THP-1 cells. 16 We tested the dose-response effect of HBM at concentrations of 1-100 μg/mL for CD14, a pattern recognition receptor, induction by RT-PCR, and observed that 20-50 μg/mL was the optimal sub-saturation range without detectable cytotoxicity. Based on these preliminary experiments, further experiments were performed using a 25 μg/mL concentration.…”
Section: Effect Of Human Breast Milk (Hbm) On Macrophage Phagocytosismentioning
confidence: 99%
“…A previous study used human milk at a 50 μg/mL concentration to study cytokine expression in THP-1 cells. 16 We tested the dose-response effect of HBM at concentrations of 1-100 μg/mL for CD14, a pattern recognition receptor, induction by RT-PCR, and observed that 20-50 μg/mL was the optimal sub-saturation range without detectable cytotoxicity. Based on these preliminary experiments, further experiments were performed using a 25 μg/mL concentration.…”
Section: Effect Of Human Breast Milk (Hbm) On Macrophage Phagocytosismentioning
confidence: 99%